Pediatric IBD patients show medication and disease activity dependent changes in NK cell and CD4 memory T cell populations - Angeliki Pappa; Julia Mührer; Patricia Gast; Sudheendra Hebbar Subramanyam; Kim Ohl; Moritz Muschaweck; Norbert Wagner; Tobias Wenzl; Klaus Tenbrock (Frontiers Media S.A., 2023)
ObjectivesCD4+ memory T cells facilitate long-termed adaptive immune responses while NK cells are predominately rapid effector cells with significant functions for both intestinal homeostasis and inflammation. We wanted to study both populations in health and pediatric inflammatory bowel disease (IBD) and correlate them with disease activity and medication.MethodsWe performed flow cytometric analyses of peripheral blood CD4 + CD45RO+ memory T cells and CD3-CD16 + CD56+ NK cells in 30 patients with IBD and 31 age-matched controls and correlated percentages of subsets with disease activity (PUCAI/PCDAI) and medication.ResultsWe found a significant reduction of peripheral NK cells in overall IBD patients with both clinical remission and disease activity, which was even more pronounced in patients treated with azathioprine. Otherwise, circulating CD4+ memory T cell populations were significantly enhanced in active IBD compared to controls. Enhancement of memory T cells was particularly found in new onset disease and correlated with disease activity scores.DiscussionOur single center cohort confirms previous results showing enhanced memory T cell populations in pediatric IBD patients, which correlate with disease activity scores. CD4+ memory T cells are a relevant pathogenic leukocyte population for disease development and perpetuation in IBD. In addition, we found a decrease of NK cells in IBD patients, which was pronounced by use of azathioprine. Surveillance of both cellular populations could possibly serve as biomarker for therapy control in pediatric IBD.